DIGITAL TRANSFORMATION OF THE MANAGEMENT MECHANISM OF A CHEMICAL INDUSTRY ENTERPRISE BASED ON ARTIFICIAL INTELLIGENCE - Chekulayeva K.A.; Achilov M.I. (Uzbekistan Open Conference, 2026)
The article examines the issues of digital transformation of the management mechanism of an industrial enterprise in the chemical sector based on artificial intelligence technologies. The necessity of integrating production data into an intelligent management system is substantiated. A mechanism is proposed that includes the analysis of production data and the prediction of equipment failures. It is shown that the use of intelligent technologies makes it possible to reduce unplanned equipment downtime and improve the efficiency of production process management.
Keywords: digital transformation; management mechanism; chemical enterprise; artificial intelligence; intelligent system; industry of Uzbekistan